2023
DOI: 10.1002/joe.22204
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory analysis of internal communication in times of the COVID‐19 pandemic

Abstract: Communication is a key element for the success of any organization. The present study aims to construct and validate a scale of perception of internal communication. It is also intended to assess whether there are differences in internal communication between employees who are teleworking and those who are in‐person work in times of the COVID‐19 pandemic. The methodology used is quantitative in nature based on a questionnaire survey, with the sample consisting of 837 Portuguese individuals in a work context. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The third article, “An exploratory analysis of internal communication in times of the COVID‐19 pandemic” by Gomes et al. (2023), extends the discussion on social innovation, honing in on workplace practices and underscoring the vital role communication plays during periods of significant social change.…”
Section: Overview Of Articlesmentioning
confidence: 97%
“…The third article, “An exploratory analysis of internal communication in times of the COVID‐19 pandemic” by Gomes et al. (2023), extends the discussion on social innovation, honing in on workplace practices and underscoring the vital role communication plays during periods of significant social change.…”
Section: Overview Of Articlesmentioning
confidence: 97%
“…(2021) posited that unambiguous communication between supervisors and subordinates is critical to conveying accurate processes, regulations, and norms while reducing employees’ anxieties. The importance of such communication is also pertinent in times of crises and disruptions (Gomes et al., 2023). Several studies also suggested that future research should focus on perceived supervisor support within organizations, particularly in non‐Western contexts that received limited attention (Charoensukmongkol, 2022; Jose & Mampilly, 2015; Mumtaz et al., 2024; Park & Jang, 2017; Ukil, 2016; Zhang et al., 2014).…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…To operationalise internal communication in the organisation, the 23 items (see Appendix A) of the internal communication perception scale developed for the Portuguese population and validated by Gomes et al (2023) were used. This scale is made up of the following dimensions: organisational information (items C6, C11, C15, C16, C17, C18, C19, C20, C22 and C23), communication with supervisors (items C2, C3, C4, C5, C7, C8, C9, C12 and C14) and communication between colleagues (items C1, C10, C13 and C21), with Cronbach's alpha values in the work by Gomes et al (2023) of 0.950, 0.945 and 0.833, respectively.…”
Section: Measuring Instrumentsmentioning
confidence: 99%